Seasonal Variability in Vadose Zone Biodegradation at a Crude Oil Pipeline Rupture Site. Issue 5 (13th May 2016) - Sihota, N.J.; Trost, J.J.; Bekins, B.A.; Berg, A.; Delin, G.N.; Mason, B.; Warren, E.; Mayer, K.U.
Abstract : Core Ideas: Contaminant mass loss rates vary seasonally. Vadose zone temperatures in the source zone correlate with rates of contaminant respiration. Natural soil respiration and gas transport seasonality affect mass loss estimates. Understanding seasonal changes in natural attenuation processes is critical for evaluating source‐zone longevity and informing management decisions. The seasonal variations of natural attenuation were investigated through measurements of surficial CO2 effluxes, shallow soil CO2 radiocarbon contents, subsurface gas concentrations, soil temperature, and volumetric water contents during a 2‐yr period. Surficial CO2 effluxes varied seasonally, with peak values of total soil respiration (TSR) occurring in the late spring and summer. Efflux and radiocarbon data indicated that the fractional contributions of natural soil respiration (NSR) and contaminant soil respiration (CSR) to TSR varied seasonally. The NSR dominated in the spring and summer, and CSR dominated in the fall and winter. Subsurface gas concentrations also varied seasonally, with peak values of CO2 and CH4 occurring in the fall and winter. Vadose zone temperatures and subsurface CO2 concentrations revealed a correlation between contaminant respiration and temperature. A time lag of 5 to 7 mo between peak subsurface CO2 concentrations and peak surface efflux is consistent with travel‐time estimates for subsurface gas migration. Periods of frozen soils coincided with depressed surface CO2 effluxes and elevated CO2 concentrations, pointing to the temporary presence of an ice layer that inhibited gas transport. Quantitative reactive transport simulations demonstrated aspects of the conceptual model developed from field measurements. Overall, results indicated that source‐zone natural attenuation (SZNA) rates and gas transport processes varied seasonally and that the average annual SZNA rate estimated from periodic surface efflux measurements is 60% lower than rates determined from measurements during the summer.